The Use of YouTube as a Supplementary Resource for Informatic Engineering Students in Speaking Skills - Sholikhi, Fu’ad; Primasari, Yusniarsi; Primasari, Fany Octa Briliani (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
The integration of audio-visual elements in educational resources has garnered significant interest, given their potential to enhance language learning efficiency. This study delves into the innovative use of such audio-visual tools, specifically YouTube, in speaking classes for students from non-English departments. The shift from conventional in-class language learning to online platforms, a change accelerated by the global Covid-19 pandemic, has revolutionized learning methodologies. This research offers a glimpse into the perspectives of ten Informatics Engineering students on utilizing YouTube videos for English language learning outside the traditional classroom setting. Employing a qualitative research methodology, the investigators conducted comprehensive interviews and classroom observations. The initial phase of data analysis involved data reduction, which was subsequently followed by further data condensation and conclusion derivation. The findings suggest that the majority of participants agreed on the significant influence of YouTube on their speaking class. Despite a handful of students facing network-related challenges, the study underscored that this web-based platform served as a valuable, cost-free supplementary resource for the speaking class.